Macroeconomic Consequences of the Funded Pension System Illusions and Realities - Camille Logeay; Volker Meinhardt; Katja Rietzler; Rudolf Zwiener (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
The pension reforms of the years 2000 until 2007 were supposed to attenuate the foreseeable effects of demographic change on the pension system. This is why the retirement age was raised, the pension level was lowered and a so-called sustainability factor ("Nachhaltigkeitsfaktor") was introduced into the pension formula. This approach meant a fundamental change of objectives - from safeguarding living standards in retirement to the stability of contribution rates. The lower future pension level is to be complemented by the subsidised formation of a private capital stock ("Riester pension") without employer participation. The analysis of the macroeconomic consequences of this reform shows that the chosen policy of enhanced funding both dampens growth and leads to insufficient income in old age. Thus the current strategy is not suitable for alleviating the demographic burden. – – Mit den Rentenreformen der Jahre 2000 bis 2007 sollten die voraussehbaren Wirkungen des demografischen Wandels auf das Rentensystem bewältigt werden. Daher wurden das Rentenalter heraufgesetzt, das Rentenniveau gesenkt und ein so genannter Nachhaltigkeitsfaktor in die Rentenformel eingefügt. Mit diesem Vorgehen wurde ein grundsätzlicher Zielwechsel eingeleitet, von der Sicherung des Lebensstandards im Rentenalter zur Beitragssatzstabilität. Das in Zukunft niedrigere Rentenniveau soll durch den staatlich geförderten Aufbau eines privaten Kapitalstocks (Riesterrente) ohne Arbeitgeberbeteiligung ausgeglichen werden. Bei der Analyse der gesamtwirtschaftlichen Folgen dieser Reformen zeigt sich, dass der gewählte Übergang zu einer verstärkten Kapitaldeckung sowohl Wachstumsprobleme erzeugt als auch zu einer ungenügenden Sicherung im Alter führt. Die bisherige Strategie ist also zur Kompensation der demografischen Belastungen ungeeignet.
Keywords: 330